The influence of benevolent leadership on knowledge sharing of postgraduate supervisor: A moderated mediating model - Li, Xiaoyu; Gao, Dongdong (Frontiers in Psychology, 2022)
In order to explore the mechanism and boundary conditions of the influence of benevolent leadership on knowledge sharing, we took postgraduate supervisor as participants and constructed a moderated mediating effect model. In this study, a total of 1,083 valid questionnaires were collected by questionnaire method and the confirmatory factor analysis, correlation analysis, regression analysis, and Hayes’s PROCESS macro were used to analyze the data. The results show that benevolent leadership positively affects knowledge sharing. Creative self-efficacy mediates the relationship between benevolent leadership and knowledge sharing. Professional identity moderates the relationship between benevolent leadership and creative self-efficacy, when the professional identity is (M − 1 SD) and (M + 1 SD), the moderating effect is significant, while when the professional identity is (M), the moderating effect is not significant. Research stress moderates the relationship between creative self-efficacy and knowledge sharing, when research stress is (M − 1 SD), (M), and (M + 1 SD), the moderating effect is significant. Professional identity and research stress jointly moderated the mediating effect of creative self-efficacy. Professional identity moderated the first half path of the mediating model, while research stress moderated the second half path of the mediating model. When the level of professional identity is high and research stress is high, benevolent leadership has the greatest positive influence on knowledge sharing through creative self-efficacy. When the level of professional identity is low and research stress is high, benevolent leadership has the greatest negative influence on knowledge sharing through creative self-efficacy. This study enriches the relevant research on benevolent leadership and knowledge sharing, explores the conditions and factors that enhance or buffer benevolent leadership, and shows that the best effect can be achieved when the leadership behavior is consistent with the situational factors.